Ovid on Cosmetics Medicamina Faciei Femineae and Related Texts - Johnson, Marguerite (Bloomsbury Academic, 2016)
The Medicamina Faciei Femineae is a didactic elegy which showcases an early example of Ovid's trademark combination of a moralistic, instructive form and trivial subject and meter. Exploring female beauty and cosmetics, with particular emphasis on the concept of 'cultus', the poem also presents five practical recipes for cosmetic treatments used by Roman women. Covering both didactic parody and pharmacological reality, this deceptively complex poem possesses wit, vivacity and importance. The first full study devoted to this little-researched but multi-faceted poem, Ovid on Cosmetics includes an in-depth introduction which situates the poem within its literary heritage of didactic and elegiac poetry, its place in Ovid's oeuvre and its relevance to social values, personal aesthetics and attitudes to female beauty in Roman society.